Peer Evaluation: Incentives and Co-Worker Relations - Joeri Sol (Tinbergen Institute, 2010)
In many workplaces co-workers have the best information about each other's effort. Managers may attempt to exploit this information through peer evaluation. I study peer evaluation in a pure moral hazard model of production by two limitedly liable agents. Agents receive a signal about their colleague's effort level, and are asked to report it to the principal. The principal may give an individual bonus for the receipt of a positive evaluation by a colleague, which stimulates effort as long as signals are revealed truthfully. A cost of lying ascertains that there can be truthful revelation. I show that interpersonal relations between colleagues constrain the bonus for receiving a positive evaluation in order to keep evaluations truthful. Still, the principal will always include such a bonus in the optimal contract, and possibly complement it with a team bonus. Co-worker relations have non-monotic effects on profits in the optimal contract.
Keywords: D86; J33; M50; 330; peer evaluation; peer appraisal; incentive contracts; co-worker relations; likeability bias; Arbeitskräfte; Soziale Beziehungen; Informationsverbreitung; Anreizvertrag; Prinzipal-Agent-Theorie